Орнитологическая ситуация на водохранилищах Днепровского каскада в летне-осенний период (на примере Киевского водохранилища) - Кистяковский, А.Б. (Вестник зоологии, 1975)
Regularities of bird migrations with day and season migrations are given with the purpose to present the data for strengthening security of plane flights in this region. The effect of meteorological, biotic and anthropic factors on the intensity and height of migrations is analyzed and results of the analysis are given.